Chicken licken: favourite tales - Stimson, Joan; Stone, Petula (Ladybird Loughborough, 1993)
When Chicken Licken goes for a walk, he is sure he can feel the sky falling in on his head. So he asks all the other animals whether they have noticed the sky?